2015
DOI: 10.1136/emermed-2014-204531
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex-dependent trends in pulmonary embolism testing and derivation of a clinical decision rule for young patients

Abstract: Young patients are frequently imaged for PE and have lower positive imaging rates than older patients. After further validation, application of our proposed rule for excluding young patients from PE imaging could reduce imaging, increase the positive rate of imaging and result in a low rate of missed PE among those excluded from imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 20 publications
1
34
0
1
Order By: Relevance
“…[14]However it is important to note that USA sites often report higher CTPA utilisation rates (20–35 per thousand adult ED attendances) than we describe here (2-15/1000). [8,23,35] It is possible there is a threshold utilisation rate beyond which yield drops dramatically without additional significant diagnoses, therefore providing minimal patient benefit, but significant increased harms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14]However it is important to note that USA sites often report higher CTPA utilisation rates (20–35 per thousand adult ED attendances) than we describe here (2-15/1000). [8,23,35] It is possible there is a threshold utilisation rate beyond which yield drops dramatically without additional significant diagnoses, therefore providing minimal patient benefit, but significant increased harms.…”
Section: Discussionmentioning
confidence: 99%
“…[8,23,35] Variations in CTPA utilisation showed no association with yield, or with size of PE, but were strongly positively correlated with increased rates of PE per 1000 adult attendances (Fig 2). This, alongside the stable small and large PE rates (compared with historical data), suggests that additional PE’s diagnosed with increased CTPA use in our region would seem to be clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were grouped together into three groups based on age 15 16 : under 18 years old, 18–35 and over 35 years of age. Highest CT positivity was found in patients under 18 (16.0%, 4/25), followed by the 18–35 group (11.7%, 36/309) and patients over 35 (10.8%, 256/2379).…”
Section: Resultsmentioning
confidence: 99%
“…CTPA positivity rate was also determined for different age (under 18, 18–35, >35) and BMI groups (under 25, 25–40, >40). Decision to stratify the age groups was done to better study different physiological groups and categorisation based on prior studies (paediatric <18 years,15 young adults 18–35 years,16 and middle-age adults and elderly >35 years). Effective dose (millisievert, mSv) was calculated for chest only examinations by the following formula: DLP (mGy·cm) × 0.014 17…”
Section: Methodsmentioning
confidence: 99%
“…One of these recommendations, regarding diagnosis of dyspepsia, is supported by 2 high-level studies; however, the recommendation regarding CT angiogram for pulmonary embolism in young patients is supported by a large number of several very low-level studies. A recent study reports that while younger patients are at a 10-fold lower risk for pulmonary embolism, they are imaged in similar proportions to elderly patients (2.3% vs 3.2%) [26]. These authors recommended a modification of the current guidelines regarding age-specific risk factors and found that it resulted in a decrease in the rate of imaging in young patients by 51%, with a missed PE rate of only 0.6%.…”
Section: Discussionmentioning
confidence: 99%